1993
DOI: 10.1246/bcsj.66.1722
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Synthesis with Nitriles: Synthesis of Some New Mercapto-Substituted Heterocycles from Alkylidenemalononitrile

Abstract: α-(Thiocyanatomethyl)benzylidenemalononitrile undergoes azo coupling with diazotized aromatic amines (ArNH2) to afford azo derivatives. The azo derivatives (Ar = Ph, 4-MeC6H4, 4-ClC6H4, 4-MeOC6H4) were readily cyclized on reflux in aqueous NaOH to 3(2H)-pyridazinimine derivatives. These latter compounds were transformed into the corresponding pyrrole derivatives on reflux in glacial acetic acid with Zn dust presumably via reductive cleavage of the N–N bond followed by recyclization with loss of ammonia. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Therefore, the reaction of 1a with 2a-d was reinvestigated under the same reaction conditions as described by Elnagdi et al [9], and found to afford solely the fully aromatic compounds 3a-d, respectively (Scheme 1). The formation of these products is in agreement with our previous work [10] as well as the authors own references cited in [9].Structures 3a-d were assigned to these reaction products on the basis of their elemental analyses as well as spectral data (see Experimental). The IR spectra of these compounds show generally two conjugated cyanoabsorption bands at t max = 2185 and 2215 cm -1 beside the amino-group absorption.…”
supporting
confidence: 89%
“…Therefore, the reaction of 1a with 2a-d was reinvestigated under the same reaction conditions as described by Elnagdi et al [9], and found to afford solely the fully aromatic compounds 3a-d, respectively (Scheme 1). The formation of these products is in agreement with our previous work [10] as well as the authors own references cited in [9].Structures 3a-d were assigned to these reaction products on the basis of their elemental analyses as well as spectral data (see Experimental). The IR spectra of these compounds show generally two conjugated cyanoabsorption bands at t max = 2185 and 2215 cm -1 beside the amino-group absorption.…”
supporting
confidence: 89%
“…Compound 14 could be obtained quantitatively from 13 upon refluxing the latter in ethanolic HCl. TLC matched the two products and no depression of melting point was obtained on admixture with 14 prepared by the present method [4,5].…”
Section: Introductionmentioning
confidence: 58%
“…In the last few years we have been involved in a program aiming to develop azoles and their fused derivatives of anticipated activity as biodegradable agrochemicals [3][4][5][6][7]. In the context of this program, some new functionally substituted pyri- dazines, polysubstituted pyrrole, and pyrrolo-fused derivatives were required.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades we have been involved in a program aiming to develop new simple procedures or novel precursors for the synthesis of heterocyclic compounds of biological interest from cheap laboratory available starting materials to be evaluated as biodegradable agrochemicals [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%